Exploring the effect of different application rates of biochar on the accumulation of nutrients and growth of flue-cured tobacco (Nicotiana tabacum) - Yang, Yingfen; Ahmed, Waqar; Ye, Chenghu; Yang, Linyuan; Wu, Lianzhang; Dai, Zhenlin; Khan, Khalid Ali; Hu, Xiaodong; Zhu, Xiaohong; Zhao, Zhengxiong (Frontiers in Plant Science, 2024)
Background: Biochar application has become one of the most potential tools to improve soil fertility and plant growth for sustainable and eco-friendly agriculture. However, both positive and negative effects of biochar application dosage have been recorded on plant growth and soil fertility. Methods: This study investigated the impact of different application rates (0, 600, 900, 1200, and 1800 kg/ha) of biochar on the soil nutrient contents, accumulation of nutrients and dry matter in different plant parts, and growth of flue-cured tobacco Nicotiana tabacum plants under field conditions. Results: Results demonstrated that soil organic carbon pool and carbon/nitrogen ratio were increased proportionally with the increasing dosage of biochar, 25.54 g/kg and 14.07 compared with control 17 g/kg and 10.13, respectively. The contents of soil total nitrogen were also significantly increased after biochar application in the middle (1.77 g/hg) and late-growth (1.54 g/kg) stages of flue-cured tobacco N. tabacum than in control (1.60 and 1.41 g/kg, respectively). The contents of soil nitrate nitrogen were also higher under low (600 and 900 kg/ha) application rates of biochar and reduced when higher (1200 and 1800 kg/ha) dosages of biochar were applied. However, it was observed that varying application rates of biochar had no impact on soil ammonium nitrogen content during the growth period of flue-cured tobacco plantsN. tabacum. The nutrient accumulation (N, P, K) in different parts of flue-cured tobacco plants N. tabacum was significantly increased under a low application rate of biochar, which enhanced the soil and plant analyzer development values, effective leaves number, growth, dry matter accumulation, and leaf yield of flue-cured tobaccoN. tabacum. In contrast, the high biochar application rate (1200 and 1800 kg/ha) negatively impacted nutrient accumulation and growth of flue-cured tobaccoN. tabacum. Conclusions: Conclusively, the optimum application of biochar (600 and 900 kg/ha) is beneficial for plant growth, soil fertility, accumulation of nutrients, and dry matter in different plant parts. However,In contrast, excessive biochar application (> 900 kg/ha) could inhibit flue-cured tobacco plant N. tabacum growth. This study provides a theoretical foundation for biochar application in tobacco and other crop production to obtain agricultural sustainability and economic stability.